Respuesta :
(sin x)/(1-cosx) + sinx/(1-cosx) =
2 csc x
We have like denominators.
Just add the numerators.
(2 sin x)/(1 - cos x) = 2 csc x
[1/(1 - cos x)](2 sin x) = 2 csc x
Take it from here.
Answer:
a ) sin x ( \frac{sinx}{cosx}*cosx- \frac{cosx}{sinx}+*cos x)= \\ sinx(sinx- \frac{cos^{2} x}{sin^{2} x})= sin^{2}x-cos^{2} x=1-cos^{2}x-cos^{2} x= \\ 1-2cos^{2}x
b ) 1 + \frac{1}{cos^{2} x} *sin^{2} x=1+ \frac{sin^{2} x}{cos^{2} x} = \\ \frac{cos {2} x+sin x^{2} x}{cos^{2} x} = \frac{1}{cos^{2} x} =sec^{2} x
c) \frac{sinx}{1-cosx} + \frac{sinx}{1+cosx}= \frac{sin x ( 1+cosx)+sinx(1-cosx)}{1-cos^{2} x} = \\ \frac{sinx+sinxcosx+sinx-sinxcosxx}{1-cos^{2}x }= \\ \frac{2sinx}{sin^{2} x} = \frac{2}{sinx}=2 csc x
d) -tan ^{2}x+sec ^{2}x=- \frac{sin ^{2} x}{cos ^{2} x} + \frac{1}{cos^{2} x} = \\ \frac{1-sin^{2x} }{cos ^{2}x }= \frac{cos^{2} x}{cos^{2}x } =1
Step-by-step explanation: